2018
DOI: 10.4103/ijn.ijn_265_17
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary neutrophil gelatinase-associated lipocalin and urinary soluble CXCL16 as biomarkers of activity in pediatric lupus nephritis

Abstract: One of the challenges of treating patients with lupus nephritis (LN) is to assess disease activity. The aim of this study was to measure the urinary neutrophil gelatinase-associated lipocalin (uNGAL) and urinary soluble chemokine (C-X-C motif) ligand 16 (CXCL16) levels in children and adolescents with systemic lupus erythematosus (SLE) and investigate whether they are elevated in active LN. This study was conducted on 80 patients diagnosed as SLE by the Systemic Lupus International Collaborating Clinics criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…This revealed a female to male ratio (7: 1). In addition, it is similar to the study carried out by El-Gamasy and El-Naghy [11] about the incidence, prevalence of JSLE and sex distribution. It shows that the prevalence was higher for girls.…”
Section: Discussionsupporting
confidence: 84%
“…This revealed a female to male ratio (7: 1). In addition, it is similar to the study carried out by El-Gamasy and El-Naghy [11] about the incidence, prevalence of JSLE and sex distribution. It shows that the prevalence was higher for girls.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, renal impairment and glucocorticoid treatment are involved in dyslipidemia in the patients with SLE. Additionally, diabetes mellitus, cardiovascular disease, liver and thyroid disease could also lead to changes in lipid profile [29][30][31]; menopaused or pregnant subjects showed increased TC and LDL-C [32]; abnormal BMI, smoking, alcohol use or taking any drugs known to influence lipid metabolism or the endocrine system could affect the results [33][34][35]. Therefore, based on these restricted inclusion criteria, our present analysis was able to assess the effects of the disease itself on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…After a series of analysis they found that SLE mice exhibited remarkable renal chemotaxis and increased renal mRNA expression of CXC chemokines such as CXCL13 and CXCL16 compared to Non SLE mice, whereas EET analog therapy altered this situation so that the mRNA expression levels of CXC chemokines and its receptors as well as immunocytes infiltration associated with kidney was decreased [90]. Other studies also clearly suggested the critical role of CXCL16 in the pathogenesis of LN and their clinical values as reliable indicator [91,92]. Hassan et al proposed that CXCL16 was an essential mediator in renal inflammation diseases like LN.…”
Section: Cxcr8mentioning
confidence: 99%